Peningkatan Peningkatan Kemampuan Reading pada Siswa SMAN 3 Atambua melalui Recount Text - Blasius Manek Koes (Universitas Cokroaminoto Palopo, 2023)
Learning English in class X Alam-1 SMA Negeri 3 Atambua specifically on the subject of reading, less attractive to students. As many as 20 students in the class generally did not dare to read the text, mispronounced words, were not fluent in reading and had low ability in translating texts. Responding to this problem, learning improvements are carried out through Recound text. The method used is Classroom Action Research through 2 cycles. In cycle 1, students are given reading texts related to Natural Sciences and each student takes turns reading the text for each paragraph. In cycle 2, students are given reading texts in the form of the History of the Proclamation of Indonesian Independence. The students were given the opportunity to sit in groups and then given the choice to read the text in front of the class or in their seats to create a fun learning atmosphere. Instruments for collecting research data using an assessment format that contains indicators and scores. The results showed that in cycle 1, the learning atmosphere was stiff and many students did not dare to read the text, misrepresented the words and did not translate the contents of the reading properly. Of the 20 students, 6% of students were categorized as very good, 9% good, 17% sufficient, 54% less, 9% low and 5% very low. In cycle 2, the results obtained were: 29% categorized very well, 29% good, 20% sufficient. For less, low and very low categories, there was a decrease in the number of students. Qualitatively, in cycle 2 the students did not feel awkward, afraid, or embarrassed. It was concluded that learning using recount text can improve the classroom atmosphere and improve student learning outcomes.